TIME's past in the present: nostalgia and the black and white image - Grainge, Paul (Cambridge University Press, 1999)
In 1995, the Hubble Space Telescope sent back to astronomers at the University of Arizona a series of vivid colour images of the Eagle Nebula, a dense formation of interstellar gas and dust the likes of which cradle newborn stars. As evidence that our perceptual universe, in every sense of the word, is defined by the representational powers of colour technology, the Hubble's “cosmic close-ups” are a clear case in point. Colour has become a standard representational form and hence the visual form. If so, what can be said of the recent popularity and proliferation of the black-and-white image?